AL-MAS'UL 'AN RA'IYYAH DALAM HADIS NABI SAW (Kajian Interpretasi Tekstual dan Kontekstual) - Mutakdir Mutakdir; Mahmuddin Mahmuddin; Tasmin Tangngareng (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2020)
This writing aims to describe al-Maus’ul ‘an Ra‘iyyah in prophet’s hadis (Textual and Contextual Interpretation Studys). Sentence al-Mas’ul ‘an Ra‘iyyah means a leader’s respomsibility. In hadith mentioned that all in the world is leader and will be asked his responsibility in here after. Human being created by Allah, has two big tasks and responsibility. First: as a servant who is obliged to increase worship. Second: as a messenger. Task and responsibility is trustworthy Allah, honestly many human being skill in carrying out the trustworthy so that responsibility report rejected by Allah. Thats why, to further analyze about al-Mas’ul ‘an Ra‘iyyah in hadith prophet saw. the auther collects meaningfull data Ra‘iyyah (leader) by searching hadith’s saw, in this process the researcher finded four terms, are term Khalifah, term Imam, term Ulim Amri dan term Sultan. Then the researcher analyzed the hadith al-Mas’ul ‘an Ra‘iyyah contained in the Sahih al-Bukhari, then Textual and Contextual Interpretation Study